Wreck : a novel [large type] - Newman, Catherine, 1968- (Harper Large Print, an imprint of HarperCollinsPublishers, 2025)
"If you loved Rocky and her family on vacation on Cape Cod, wait until you join them at home two years later. (And if this is your first meeting with this crew, get ready to laugh and cry--and relate.)Rocky, still anxious, nostalgic, and funny, is living in Western Massachusetts with her husband Nick and their daughter Willa, who's back home after college. Their son Jamie has taken a new job in New York, and Mort, Rocky's widowed father, has moved in. It all couldn't be more ridiculously normal--until Rocky finds herself obsessed with a local accident that only tangentially affects them--and with a medical condition that, she hopes, won't affect them at all"--